Effect of phosphorus and potassium on growth and yield parameters and disease incidence of potato - MOHAMMAD SAIDUL ISLAM; ABU ASHRAF KHAN; MD. TANBIR RUBAYET; MD. MOYNUL HAQUE; MD. ABDUL KARIM; ISMAIL HOSSAIN MIAN (Nusantara Bioscience, 2025)
Abstract. Islam MS, Khan AA, Rubayet MT, Haque MM, Karim MA, Mian IH. 2025. Effect of phosphorus and potassium on growth and yield parameters and disease incidence of potato. Nusantara Bioscience 17: 313-321. A study was undertaken to find out the effects of two macronutrient elements on plant growth, tuber, and tuber disease incidence of potato (Solanum tuberosum). The major nutrient elements were phosphorus (P) and potassium (K). The doses of nutrients were P @ 0, 20, 35, 50 kgha-1, and K @ 0, 90, 140, 190 kgha-1. Data were recorded on vine number/ten hills, plant height, canopy coverage, tuber number per ten plants, and tuber weight per plot. Disease incidence and physiological disorders such as common scab (Streptomyces scabies), dry rot (Fusarium sp.) and soft rot (Erwinia carotovora) of potato were also assessed. The highest tuber yield of 24.05 (44.53 tha-1) and 24.12 kg plot-1 (44.66 tha-1) was obtained with 35 kgha -1 P and 140 kgha-1 applied individually. When both the elements were applied together, the highest yield of 30.68 kg plot-1 (56.82 tha-1) was obtained at 35 kg P and 140 kg K per hectare. Tuber diseases and disorders were minimal when 35 kgha-1 P and 140 kgha-1 K were applied together during the potato cultivation under field conditions. Based on findings of the present study, it may be concluded that application of P and K at the rates of 37.67 and 136.69 kgha-1 along with a standard dose of N is optimum for maximum plant growth, tuber yield and minimizing the incidence of disease and disorders of potato tuber.